Analysis of Ultra Fine Bubble Addition on Biodiesel Fuel to Reduce Emission of Two Wheel Tractors Diesel Engine - Hanifa Farafisha; Sam Herodian; Anto Tri Sugiarto; Riesta Anggarani; Joko Pitoyo; Yogi Pramudito (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Diesel engines are known as high efficiency engines and are used in public transportation and agricultural sector. The exhaust gas produced by diesel engines is dangerous for human health. Ultra Fine Bubble (UFB) technology which is currently being developed is an emission reduction alternative that can enrich oxygen in fuel and has the potential to reduce emissions. This research was carried out to apply UFB technology to a variety of fuels and compare the emission results. This research method is data collection based on experimental tests. The types of fuel used in this research are biodiesel and biodiesel-diesel mixture. The research procedure starts from instrument preparation, fuel inflation which produces UFB fuel, fuel characteristics, instrument performance testing and data processing. The characteristic testing method follows the American Standard Testing and Materials (ASTM) and performance testing follows the ISO/IEC 17025:2017 standard. The research results show that fuel treated with ultra-fine bubbles can reduce exhaust emissions compared to fuel without UFB. CO content decreased by 608 parts per million (ppm) in the biodiesel-diesel blend and 306 ppm in biodiesel with UFB. The exhaust gas temperature becomes stable when the fuel contains bubbles and reduces NO and NOx content in emissions. Keywords: Biodiesel, Diesel engine, Fuel, Ultra fine bubble